การสกัดเพคตินจากส่วนต่าง ๆ ของกล้วย - ปุญญพัฒน์ อุทิศผล (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
Pectin is a complex polysaccharide which are used as gelling agent, thickening agent and stabilizer in food and it is also a dietary fiber that reduces blood sugar. Pectin is fiber found in the fruit’s peel, such as citrus peel, apple pomace and banana peel. Banana stem and banana peels are waste. Therefore, this research is interested to extract pectin from banana peel and banana stem of Kluay Nam Wa by comparison with source of commercial pectin, mandarin orange peel, which were extracted under the same extraction conditions. The yield of orange peel was 31.07 ± 0.9% dry weight. While pectin from Banana peel and banana stem were 4.67 ± 0.2% and 3.45 ± 0.3% dry weight, respectively. Pectin extracted from banana peel, banana stem and orange peel have pectin methoxyl content 7.46 ± 0.48%, 6.62 ± 0.46% and 6.27 ± 0.07%, respectively. The extracted banana peel pectin and banana stem pectin were categorized as low methoxyl pectin with the degree of esterification 37.08 ± 1.72% and 33.91 ± 1.34%, respectively, while orange peel pectin was high methoxy pectin (76.50%). The anhydrouronic acid (AUA) content of pectin from banana peel, banana stem and orange peel were 46.30 ± 0.43%, 40.05 ± 3.74% and 65.63± 2.54%, respectively. The antioxidant activity of pectin extracted from banana peel, banana stem and orange peel were investigated by ABTS and FRAP method. The results showed that pectin from banana peel were 23.45 ± 1.30 mM VCEAC/g and 1.50 ± 0.09 mM TEAC/g, respectively, which were significantly (p <0.05) higher than those from banana stem and orange peel in both ABTS and FRAP methods. The antioxidant activity of banana stem and orange peel by ABTS method were 9.68 ± 0.88 and 7.17 ± 0.57 mM VCEAC/g and FRAP methods were 0.74 ± 0.04 and 0.69 ± 0.02 mM TEAC/g, respectively. The antioxidant activity in pectin extracted from banana peel and was significantly higher than those from banana stem and orange peel. For the prebiotic activity of pectin extracted from banana peel, the survival of probiotic L. paracasei and B. lactis Bb12 in pomegranate juice with pectin-added for 14 days were 6.20 ± 0.02 and 5.71 ± 0.004 log CFU/ml, respectively, whereas the microbial contents of the test tube without pectin were 4.24 ± 0.04 and 4.18 ± 0.14 log CFU/ml, respectively. Therefore, the use of pectin from banana peels is interesting to research further.